Implicit Theories of Child Sexual Exploitation Material Offenders: Cross-Cultural Validation of Interview Findings - Soldino, Virginia (International journal of offender therapy and comparative criminology, 2020)
Offense-supportive cognitions are thought to result from underlying implicit theories (ITs). As child sexual exploitation material (CSEM) users are a distinct type of sex offender, Bartels and Merdian proposed that CSEM offenders hold five different ITs from those endorsed by contact sex offenders (i.e., Unhappy World, Self as Uncontrollable, Child as Sexual Object, Nature of Harm [CSEM variant], and Self as Collector), linked by an assumption about the Reinforcing Nature of the Internet. This article reports a conceptual content analysis of 23 interviews conducted with CSEM offenders in the United Kingdom and Spain. Support for all CSEM-specific ITs was found across both samples, providing an empirical validation of this conceptualization. Finally, four ITs originally identified for contact sex offenders were also identified, namely, Uncontrollability, Child as Sexual Being, Dangerous World, and Nature of Harm. Further validation of CSEM-related ITs is encouraged.